Alveolar ridge dimensional changes following ridge preservation procedure using SocketKAP™: exploratory study of serial cone‐beam computed tomography and histologic analysis in canine model. Issue 9 (13th December 2015) - Ryu, Kyung‐Ho; Min, Seiko; You, Hyung‐Keun; Sin, Yeon‐Woo; Lee, Wan; Lee, Jun; Kiss, Alex; Almohaimeed, Mohammad; Zadeh, Homayoun H.
Abstract: Introduction: The aim of this pilot study was to examine the kinetics of alterations in alveolar ridge width and height following tooth extraction with and without ridge preservation, using anorganic bovine bone mineral (ABBM) and a novel device (SocketKAP ™ ) designed for obturation of socket orifice. Materials and methods: Maxillary left and right PM1 and mandibular right PM2 and PM4 were extracted on six beagle dogs and treated as follows: Group A: negative control; Group B: SocketKAP ™ alone; Group C: ABBM + SocketKAP ™ . Serial cone‐beam computed tomography (CBCT) was taken at 0‐, 1‐, 2‐, 4‐, 8‐ and 12‐week intervals to calculate the rate of alveolar bone loss, followed by histologic and histomorphometric analyses at 12 weeks. Across group outcomes were compared. Results: Without additional intervention, the crestal‐most 3 mm of alveolar bone width lost approximately 0.21–0.28 mm per week. The rate of alveolar buccal bone height loss was 0.19 mm per week. Comparatively, in group C, the alveolar bone was relatively stable, with loss of only 0.003–0.13 mm of width and 0.12 mm of height per week. These differences were statistically significant. The alveolar bone in sites treated by SocketKAP ™ alone was significantly different from control only at select time points and locations of the ridge, presumably due to small sample size. Conclusion: Without additional intervention, tooth extraction was accompanied by rapid loss of alveolar ridge width and height. Applications of SocketKAP ™ and ABBM were effective in reducing alveolar crestal width and height loss following tooth extraction.